Lrig1 regulates the balance between proliferation and quiescence in glioblastoma stem cells - Ferguson, Kirsty M.; Blin, Carla; Alfazema, Neza; Gangoso, Ester; Pollard, Steven M.; Marques-Torrejon, Maria Angeles (Frontiers in Cell and Developmental Biology, 2022)
Patients with glioblastoma (GBM) face a dismal prognosis. GBMs are driven by glioblastoma stem cells (GSCs) that display a neural stem cell (NSC)-like phenotype. These GSCs are often in a quiescent state that evades current therapies, namely debulking surgery and chemo/radiotherapy. Leucine-rich repeats and immunoglobulin-like domains (LRIG) proteins have been implicated as regulators of growth factor signalling across many tissue stem cells. LRIG1 is highly expressed in gliomas and importantly, polymorphisms have been identified that are risk alleles for GBM, which suggests some functional role in gliomagenesis. We previously reported that Lrig1 is a gatekeeper of quiescence exit in adult mouse NSCs, suppressing EGFR signalling prior to cell cycle re-entry. Here, we perform gain- and loss-of-function studies to understand the function of Lrig1 in GSCs. Using a novel mouse GSC model, we show that genetic ablation of Lrig1 in cultured GSCs results in higher proliferation and loss of quiescence. In vivo, mice transplanted with GSCs lacking Lrig1 display lower survival compared to Lrig1 WT GSCs, with tumours displaying increased proportions of proliferative cells and reduced quiescent subpopulations. In contrast, Lrig1 overexpression in mouse GSCs results in enhanced quiescence and reduced proliferation, with impaired tumour formation upon orthotopic transplantation. Mechanistically, we find that Lrig1-null cells have a deficiency in BMP signalling responses that may underlie their lack of responsiveness to quiescence cues in vivo. These findings highlight important roles for Lrig1 in controlling responsiveness to both EGFR and BMPR signalling, and hence the proportions of quiescent and proliferative subpopulations in GBMs.